2022
DOI: 10.3389/fspas.2022.896632
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Identification and Classification of Solar Granulation Structures Using Semantic Segmentation

Abstract: Solar granulation is the visible signature of convective cells at the solar surface. The granulation cellular pattern observed in the continuum intensity images is characterised by diverse structures e.g., bright individual granules of hot rising gas or dark intergranular lanes. Recently, the access to new instrumentation capabilities has given us the possibility to obtain high-resolution images, which have revealed the overwhelming complexity of granulation (e.g., exploding granules and granular lanes). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Dense segmentation of photospheric images has been pursued recently by Díaz Castillo et al (2022), with the aim of classifying granular structures. The access to high-resolution images has shown the overwhelming complexity of granulation.…”
Section: Segmentation Of Solar Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dense segmentation of photospheric images has been pursued recently by Díaz Castillo et al (2022), with the aim of classifying granular structures. The access to high-resolution images has shown the overwhelming complexity of granulation.…”
Section: Segmentation Of Solar Imagesmentioning
confidence: 99%
“…One can only hope to understand the physical mechanisms by first applying a semantic segmentation of the images and isolating interesting phenomena (intergranular lanes, exploding granules, ...). Although it is still work in progress, Díaz Castillo et al (2022) demonstrated that a U-Net is able to learn this segmentation problem and then apply it to large datasets to analyze the statistical properties of magnetoconvection.…”
Section: Segmentation Of Solar Imagesmentioning
confidence: 99%